Studi Meta Analisis Efektivitas Media Pembelajaran terhadap Hasil Belajar Siswa SMK - Elfi Tasrif; Yasdinul Huda; Liza Mustika Sari; Misrol Ayani (Departement of Mathematics Education, 2023)
Learning media is a tool that can convey a message to someone, the message conveyed is expected to be easily understood and adapted to needs. Vocational High School students have learning needs, one of which is a learning style, namely Audio Visual and Visual. The media studied in this study are Audio-visual and visual media, such as animation-based media, YouTube, interactive videos, Prezi, Android-based and others to support teachers in the learning process. The usefulness of this research is to find out how the effectiveness of learning media is on student learning outcomes. This type of research is meta-analysis with quantitative procedures. The information was gathered from 20 journals that were found on Google Scholar and Sinta. The value of 2.30 is in the very high category according to the effects size analysis based on the audio-visual media type category, and the visual effect size media type is in the very high category with a value of 1.37. had a very high category average effect size of 1.85. According to data analysis findings, students' learning outcomes in vocational schools are significantly impacted by the usage of audio-visual technology in the classroom.